PEMBERDAYAAN MASYARAKAT DALAM PENGELOLAAN SAMPAH TERPADU MENUJU DESA MANDIRI DAN BERKELANJUTAN - Muliatie, Yurilla Endah; Jum’ati, Nurleila; Riawan Putra, Muchamad Hengki; Sigit, Larasati Ramadhani; Lusanti, Fitri Dhea; Fathuloh, Fathuloh; Redarkum, Gading Dinda; Abdul Aziz, Mochamad; Wahyuni, Putri; Sunarko, Steffy Gihon; Yuliani, Ella Erwinda (Asosiasi Sinergi Pengabdi dan Pemberdaya Indonesia (ASPPI), 2025)
The problem of waste management at the village level is a critical issue that directly impacts the environment, health, and economy of the community. Sukoreno Village, Prigen District, Pasuruan Regency, produces 2–2.5 tons of waste per day, mostly from households and home industries, but its management is still carried out conventionally without sorting. This condition causes environmental pollution and closes the opportunity to utilize waste as a resource. This community service activity aims to increase environmental awareness and literacy among residents, build local institutions in the form of a waste bank and 3R TPS, introduce appropriate technology, and encourage the creation of small waste-based business units towards an independent and sustainable village. The method used is Participatory Action Research (PAR) through five systematic stages: problem identification, socialization, core program implementation, monitoring and evaluation, and strengthening sustainability. The results of the activity show increased community participation in waste sorting, the establishment of a waste bank and 3R TPS, the implementation of plastic shredding machines, as well as the development of composting businesses, maggot cultivation, and creative products from plastic waste. This program has successfully established a participatory, productive, and efficient waste management ecosystem, enabling it to be replicated in other villages as a model for integrated waste management based on a circular economy.